Perspectives of people with spinal cord injury on a pain education resource - Fernandez, Gabriel E.; Anderson, Kim D.; Vastano, Roberta; Frank, Scott I.; Robayo, Linda E.; Cherup, Nicholas P.; Kochen, William; Widerström-Noga, Eva (Frontiers in Public Health, 2024)
Introduction Spinal cord injury (SCI) often leads to neuropathic pain that negatively affects quality of life. Several qualitative research studies in individuals with SCI who experience neuropathic pain indicate the lack of adequate information about pain. We previously developed an educational resource, the SeePain, based on scientific literature and a series of qualitative interviews of people with SCI, their significant others/family members, and SCI healthcare providers. Methods However, to quantitatively evaluate the utility of this educational resource in a larger sample, we examined the agreement and usefulness ratings of statements regarding clarity/comprehensibility, content, and format of the SeePain, derived from the thematic analysis of our previous qualitative interviews. Participants completed a survey that provided a digital version of the SeePain and then rated their agreement/usefulness with the statements using numerical rating scales. Results There were overall high perceived agreement and usefulness ratings regarding the SeePain’s clarity, content, and format. A factor analysis reduced the agreement and usefulness ratings into 4 components (content, clarity, format, and delivery medium). Group comparisons showed that individuals with higher education were more likely to endorse electronic and website formats, and the usefulness of a shorter version of the SeePain; females and younger individuals showed greater endorsement for clarity. Finally, higher pain intensity ratings were associated with greater agreement and usefulness of the content of the SeePain. Discussion Overall, these results support the utility of the SeePain as a source of information regarding pain that may facilitate communication about pain and its management following SCI.